Pengaruh Pengetahuan Perpajakan, Sosialisasi Pajak Dan Tarif Pajak Terhadap Kepatuhan Wajib Pajak UMKM Di Kota Medan - Purba, Rosanna; Ginting, Rika Mei Hayani; Harefa, Hilda Syafaini; Lembeng, Rani Novia S (JURNAL MUTIARA AKUNTANSI, 2023)
This study aims to examine the effect of tax knowledge, tax socialization and tax rates on MSME taxpayer compliance in Medan city both partially and simultaneously. The method used is a descriptive method with a quantitative approach. This study used a simple random sampling method. With a population of 1,825 MSMEs in Medan City. The data collection technique used was by distributing questionnaires to 95 MSMEs. The data analysis technique used is multiple linear regression. The results showed that tax knowledge and tax rates partially had a positive and significant effect on MSME taxpayer compliance in Medan City, while tax socialization partially had no effect on MSME taxpayer compliance in Medan City. Simultaneously, tax knowledge, tax socialization, and tax rates have a positive and significant effect on MSME taxpayer compliance in Medan City.